Continuous 3D-nanopatterned Ni–Mo solid solution as a free-standing electrocatalyst for the hydrogen evolution reaction in alkaline medium. Issue 12 (5th March 2021) - Kim, Kisun; Tiwari, Anand P.; Hyun, Gayea; Yoon, Yeoheung; Kim, Heeyoung; Park, Jeong Young; An, Ki-Seok; Jeon, Seokwoo
Abstract : A free standing 3D-nanopatterned solid solution of Ni–Mo has been fabricated for excellent hydrogen evolution reaction (HER) activity. Abstract : To date, researchers have shown that nanostructured solid solutions of transition metal electrocatalysts can improve hydrogen evolution reaction (HER) activity in alkaline media. However, there are few reports that focus on mass producing efficient electrocatalysts for the HER based on continuous 3-dimensional (3D) nanopatterning. Herein, a 3D-nanopatterned solid solution of Ni–Mo is synthesized to provide efficient electrocatalytic activity in alkaline electrolytes. Experimentally, it is found that the electrochemically active surface area (ECSA) is 65 times higher than that of 2D Ni–Mo. Additionally, the charge transfer resistance ( R ct ) of 3D Ni–Mo (0.6 Ω) is 16 times lower than that of 2D Ni–Mo (10.3 Ω), which shows that 3D Ni–Mo allows the fast transport of ions and facilitates the H* desorption process; thus, the above result contributes to the improved kinetics for HER activity. Moreover, the 3D-nanopatterned Ni–Mo electrocatalyst requires a minimum overpotential of 39 mV to achieve a 10 mA cm −2 current density, which is very close to that of the benchmark Pt/C electrocatalyst (30 mV) for the HER in alkaline media. In addition, the 3D-nanopatterned Ni–Mo electrocatalyst exhibits 94.7% faradaic efficiency during the HER. The as-prepared 3D-nanopatterned Ni–Mo is a free-standing electrocatalyst that can be synthesized at the inch scale or even larger and will be useful for practical applications in future renewable energy devices.